Network Analysis Combining Proteomics and Metabolomics Reveals New Insights Into Early Responses of Eucalyptus grandis During Rust Infection - Sekiya, Alline; Marques, Felipe Garbelini; Leite, Thiago Falda; Cataldi, Thais Regiani; de Moraes, Fabricio Edgar; Pinheiro, Ana Lúcia Mendes; Labate, Mônica Teresa Veneziano; Labate, Carlos Alberto (Frontiers in Plant Science, 2021)
Eucalyptus rust is caused by the biotrophic fungus, Austropuccinia psidii, which affects commercial plantations of Eucalyptus, a major raw material for the pulp and paper industry in Brazil. In this manuscript we aimed to uncover the molecular mechanisms involved in rust resistance and susceptibility in Eucalyptus grandis. Epifluorescence microscopy was used to follow the fungus development inside the leaves of two contrasting half-sibling genotypes (rust-resistance and rust-susceptible), and also determine the comparative time-course of changes in metabolites and proteins in plants inoculated with rust. Within 24 h of complete fungal invasion, the analysis of 709 metabolomic features showed the suppression of many metabolites 6 h after inoculation (hai) in the rust-resistant genotype, with responses being induced after 12 hai. In contrast, the rust-susceptible genotype displayed more induced metabolites from 0 to 18 hai time-points, but a strong suppression occurred at 24 hai. Multivariate analyses of genotypes and time points were used to select 16 differential metabolites mostly classified as phenylpropanoid-related compounds. Applying the Weighted Gene Co-Expression Network Analysis (WGCNA), rust-resistant and rust-susceptible genotypes had, respectively, 871 and 852 proteins grouped into 5 and 6 modules, of which 5 and 4 of them were significantly correlated to the selected metabolites. Functional analyses revealed roles for photosynthesis and oxidative-dependent responses leading to temporal activity of metabolites and related enzymes after 12 hai in rust-resistance; while the initial over-accumulation of those molecules and suppression of supporting mechanisms at 12 hai caused a lack of progressive metabolite-enzyme responses after 12 hai in rust-susceptible genotype. This study provides some insights on how E. grandis plants are functionally modulated to integrate secondary metabolites and related enzymes from phenylpropanoid pathway and lead to temporal divergences of resistance and susceptibility responses to rust.